PARE0005 Brief Overview of ENCA (European Network for Children with Arthritis). (15th July 2016) - Egert, Y.; Costello, W.; Kepic, M.
Abstract : Background: ENCA, the European Network for Children with Arthritis was founded in 2002 by parents representing national JIA (Juvenile Idiopathic Arthritis) associations from several European countries. ENCA is a broad based association that covers JIA and other orphan joint associated conditions. It is run on a voluntary basis by parents who wish to advance the quality of treatment their children receive through networking, communications and research. ENCA is associated with the Paediatric Rheumatology European Society (PReS) the European scientific society for healthcare professionals in the field of paediatric rheumatology. ENCA is structured as an informal network between national JIA associations, and is open to all JIA associations. Objectives: As an international networking group, ENCA's role is to gather and circulate information, knowledge, and expertise gathered by individual associations in order to promote knowledge and positive practices among all the associations. This knowledge, in turn, filters down through the national associations to medical systems, parents and sick children, thus upgrading the quality of care offered in each country. ENCA has three strategic themes: Exchange information about the activities of each association Promote common projects at European level Set up information networks and regular exchanges between associations Methods: Member associations are asked to send representatives to the yearly ENCA conference which takes place in conjunction with the PReS (every 4th year also as part of Eular). A website, closed Facebook group and a yahoo group allow members to have constant communication. International networking helps solve problems faced by all organizations on a national level and parents on an individual level. Pooling resources can help weaker countries acquire better treatment and social services by belonging to an International organization. In addition ENCA collaborates with Doctor Organizations and research establishments to promote, initiate and facilitate research aimed to advance sick children's needs. Results: Since its inception, ENCA has made advances in both fields: communication between the associations, and research with the medical establishment. Establishing communications between the associations has proven itself as an effective method for solving common problems faced by children in all countries, as well as an opportunity to bring information to the fore. In addition, ENCAs' cooperation with PReS and PRINTO have facilitated two important projects: The SHARE parents' survey initiated by PReS to collect information about the quality of care of JIA patients. The study was conducted through ENCA, allowing for a wider resource base and more accurate results. In addition, ENCA facilitated the translation of the new upgraded PRINTO (The European Union site for information on paediatric rheumatic diseases) site into national languages, thereby enabling access of up to date information to parents. Conclusions: As parents of children with JIA, ENCA has greatly increased our knowledge within all areas of health and social care. It has given us a diverse network allowing us access to a broad source of expertise, knowledge and resources. Through pooled resources it has helped weaker organizations. Acknowledgement: PReS, Share, Printo Disclosure of Interest: None declared